Natural active botanical metabolites: targeting AMPK signaling pathway to treat metabolic dysfunction-associated fatty liver disease - Wang, Hualing; Liu, Xinyu; Wang, Chunyi; Yu, Shishuang; Yang, Xiuli; Cao, Xiyu; Luo, Maocai; Liu, Shiwei; Zhang, Chuantao (Frontiers in Pharmacology, 2025)
Metabolic dysfunction-associated fatty liver disease (MAFLD), also known as non-alcoholic fatty liver disease (NAFLD), has emerged as one of the most common chronic liver diseases globally, with a tendency to progress gradually. With persistent disease progression, it may subsequently manifest as complications, including non-alcoholic steatohepatitis (NASH), cirrhosis, and liver cancer, and has been clinically established as a primary causative factor for liver failure and clinical scenarios necessitating liver transplantation. AMP-activated protein kinase (AMPK) is the central regulatory hub governing cellular energy homeostasis. It plays a central regulatory role in improving lipid metabolic disorders and represents a key molecular nexus for the management of MAFLD. Currently, the pathogenesis of MAFLD remains unclear, and treatment options are still limited, posing a significant public health challenge. Natural active botanical metabolites, which are important sources of novel therapeutic drugs, are widely available in nature and characterized by strong practicability and low cost. Growing evidence suggests that natural active botanical metabolites have definite therapeutic effects on MAFLD and hold broad application prospects. This study aims to systematically review in vivo and in vitro experimental evidence on natural active botanical metabolites targeting the AMPK pathway for the treatment of MAFLD. Based on our research findings, it is anticipated that effective natural active botanical metabolites can be incorporated into novel formulations in the future, which are expected to facilitate its bench-to-bedside transformation.